In-vivo microscopy reveals the impact of Pseudomonas aeruginosa social interactions on host colonization - Rezzoagli, Chiara (ISME J, 2019)
Pathogenic bacteria engage in social interactions to colonize hosts, which include quorum-sensing-mediated communication and the secretion of virulence factors that can be shared as “public goods” between individuals. While in-vitro studies demonstrated that cooperative individuals can be displaced by “cheating” mutants freeriding on social acts, we know less about social interactions in infections. Here, we developed a live imaging system to track virulence factor expression and social strain interactions in the human pathogen Pseudomonas aeruginosa colonizing the gut of Caenorhabditis elegans. We found that shareable siderophores and quorum-sensing systems are expressed during infections, affect host gut colonization, and benefit non-producers. However, non-producers were unable to successfully cheat and outcompete producers. Our results indicate that the limited success of cheats is due to a combination of the down-regulation of virulence factors over the course of the infection, the fact that each virulence factor examined contributed to but was not essential for host colonization, and the potential for negative frequency-dependent selection. Our findings shed new light on bacterial social interactions in infections and reveal potential limits of therapeutic approaches that aim to capitalize on social dynamics between strains for infection control.